The Tenuous Visibility and Delusion in the Image of pine trees in Painting from the State of Paraná (Palíndromo, 2022)
This article intends to investigate images of pine trees in paintings from State of Paraná. It starts with works by several artists from the State, from different periods and contexts, in which the relationships of the detail in the work and the work in detail are observed, as well as the approach of the “patch” and the singularities of this figure. Georges Didi-Huberman's reflections about “the Aporia of Detail” and “Patch” give support for thinking about the intermittent image of the pine tree; in its minimal, ghostly, tenuous, diluted and illusional appearances. Also, the pine tree is presented as a process of accumulating space, time and memory, that implies the difference and the repetition, the symptom and the opening of the image in its relationship with history, in the summons of a past and/or future, which interrupts the linear time.
Keywords: Patch; Detail; Pine tree in art